PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF DEVELOPING STUDENTS' ALGORITHMIC THINKING IN THE CONTEXT OF PROGRAMMING (International Educators Conference, 2025)
This article analyzes the works of scholars on developing algorithmic thinking in general secondary school students and examines the pedagogical and psychological aspects of fostering students' algorithmic thinking in the field of programming.